68Ga-labeled fluorinated benzamide derivatives for positron emission tomography imaging of melanoma - Chaewon Lee; Boreum Song; Eunsu Kim; Yejin Seo; Dagyeong Hong; Jiyu Kim; Wookyeong Jeong; Seong-Young Kwon; Dong-Yeon Kim; Ayoung Pyo (PLoS ONE, 2025)
Malignant melanoma tends to aggressively metastasize, resulting in it being a potentially lethal form of skin cancer with high mortality rates. The advanced stages of melanoma have a very poor prognosis because of the high tendency for metastasis, and there is therefore, a strong desire to develop efficient technology for the early detection of melanoma. The benzamide structure, which contains aromatic ring and amine group, exhibits a high affinity for melanin, making it a promising agent for targeting melanoma in diagnostic and therapeutic applications. In this study, we synthesized a fluorinated benzamide derivative and chelated it with the radioisotope 68Ga to detect melanoma on positron emission tomography (PET) imaging, and then evaluated its biological properties. We synthesized the new probe 2,2’,2,”2”’-(2-(4-(3-(2-((2-(5-fluoropicolinamido)ethyl)(methyl)amino)ethyl)thioureido)benzyl)-1,4,7,10-tetraazacyclododecane-1,4,7,10-tetrayl)tetraacetic acid (MI-0202C1) for melanoma imaging from 5-fluoropyridine-2-carboxylic acid and conjugated 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA) for chelation with 68Ga. The radiochemical yield and radiochemical purity of the 68Ga chelation complex were confirmed by radio-thin layer chromatography (radio TLC). In vitro cellular uptake of 68Ga-MI-0202C1 was verified in B16F10 cells (murine melanoma). In vivo distribution and small animal PET studies were conducted on mice bearing B16F10 xenografts. The MI-0202C1 was chelated with 68Ga at 90°C for 10 min at pH 5, resulting in a radiochemical yield and radiochemical purity of over 95%. The cellular uptake of 68Ga-MI-0202C1 over 60 min was higher in a group treated with L-tyrosine (2 mM) than in a non-treated group, indicating selective uptake of melanin. 68Ga-MI-0202C1 successfully visualized B16F10 xenografts in microPET imaging performed at 30 and 60 min after intravenous injection, suggesting that 68Ga-MI-0202C1 has considerable potential as a diagnostic probe for melanoma.